2019
DOI: 10.1111/os.12423
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted Minimally‐invasive Internal Fixation of Pelvic Ring Injuries: A Single‐center Experience

Abstract: Objective To investigate the indications, surgical strategy and techniques, safety, and efficacy of robot‐assisted minimally‐invasive internal fixation of pelvic ring injuries. Methods The clinical data of 86 patients with anterior and posterior pelvic ring injuries who underwent robot‐assisted minimally‐invasive internal fixation were retrospectively analyzed. The patients included 57 men and 29 women aged between 22 and 75 years, with an average age of (40.2 ± 13.6) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…Currently, the navigation technique has been demonstrated to be optimal for percutaneous placement of the sacroiliac screw to achieve accurate and efficient results. In addition, internal fixation under robotic guidance can reduce the frequency of intraoperative fluoroscopy use, especially with the TiRobot orthopedic surgery robot, which was made in China [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the navigation technique has been demonstrated to be optimal for percutaneous placement of the sacroiliac screw to achieve accurate and efficient results. In addition, internal fixation under robotic guidance can reduce the frequency of intraoperative fluoroscopy use, especially with the TiRobot orthopedic surgery robot, which was made in China [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, excessive radiation exposure to patients and medical staff can cause great harm to their bodies. Compared with the non-navigation surgery, orthopaedic surgery under navigation guidance, especially with robot-aided technology, shows significantly better accuracy on screw positioning and less radiation damage [12][13][14] .…”
mentioning
confidence: 99%
“…For pelvic ring fractures, 3 studies reported patient outcomes after a follow-up period using the Majeed score (Table 4 ). [ 23 , 24 , 26 , 29 ] The overall outcomes were excellent or good in both the robot and conventional surgery group, and there were no statistically significant differences between groups. [ 23 , 24 , 26 ] For hip fractures, the Harris Hip Score was used to measure functional outcome in 3 studies investigating hip fractures.…”
Section: Resultsmentioning
confidence: 99%